Modularity of music: evidence from a case of pure amusia. Issue 4 (1st October 2000) - Piccirilli, Massimo; Sciarma, Tiziana; Luzzi, Simona
Abstract : A case of pure amusia in a 20 year old left handed non-professional musician is reported. The patient showed an impairment of music abilities in the presence of normal processing of speech and environmental sounds. Furthermore, whereas recognition and production of melodic sequences were grossly disturbed, both the recognition and production of rhythm patterns were preserved. This selective breakdown pattern was produced by a focal lesion in the left superior temporal gyrus. This case thus suggests that not only linguistic and musical skills, but also melodic and rhythmic processing are independent of each other. This functional dissociation in the musical domain supports the hypothesis that music components have a modular organisation. Furthermore, there is the suggestion that amusia may be produced by a lesion located strictly in one hemisphere and that the superior temporal gyrus plays a crucial part in melodic processing.